Orthodontic camouflage treatment of Class III malocclusion. Case report - Ypanaque Ramirez, Loidy Liceth (2019)
From the orthodontic and maxillofacial point of view, a malocclusion with a severe skeletal disharmony can be treated with an orthopedic, orthodontic and/or orthognathic approach; however, some adult patients reject the surgical option, in those cases, orthodontic camouflage might be the only alternative. This article reports the orthodontic camouflage of a 21 year and 2 months old male patient with a Class III low angle skeletal pattern, edge to edge anterior bite relationship and decresead lower facial third. A modified utility arch, posterior acrylic bite block, Class III intermaxillary elastics, multiloop archwire and lower interproximal reduction were used. After 26 months of treatment, Class I molar and canine relationship with functional overbite and overjet was achieved. In addition, reduction of lower lip protrusion, greater exposure of upper incisors at smile and a pleasant facial profile was obtained. 11 months follow up reveals stability of the results.